PENINGKATAN HASIL BELAJAR MELALUI PENERAPAN METODE MIND MAPPING DAN PENILAIAN PERFORMANSI DENGAN TEKNIK PEER ASSESMENT PADA MATA KULIAH BIOLOGI SEL - Kamalia Fikri (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2015)
The aim of this research is to determine the increasing of learning through the mind mapping method and performance assessment with peer assessment technique in cell biology subject. This research is a class room action research that consist of four phase includes planning, action, observation, and reflection. The result showed that there are some increasing of learning outcome, 38.38% from prasiklus to cycle 1, and 19.49% from cycle 1 to cycle 2. Key words: mind mapping, performance, peer assesment, cell biology